2021
DOI: 10.31234/osf.io/c9sgb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rhythm Comes, Rhythm Goes: Short-Term Periodicity of Prosodic Phrasing

Abstract: Speech is perceived as a sequence of meaningful units. Speech prosody helps to delimit these units through pauses and acoustic modulations of pitch, amplitude and speech rate. These prosodic boundaries subdivide utterances into prosodic phrases. To be understood, prosodic phrases must obey cognitive and neurobiological constraints on the side of the listener. In particular, the neurobiological substrates of speech processing have been argued to operate periodically—with one electrophysiological processing cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Our findings concerning rhythmicity are also in line with previous adult studies that have contextualized the temporal regularities of speech within local (utterance level) stress patterns (Arvaniti, 2009;Nolan & Jeon, 2014;Tilsen & Arvaniti, 2013). Indeed, there is recent evidence for local prosodic stress regularities in ADS in different languages (e.g., Inbar et al, 2020;Stehwien & Meyer, 2021). The slower syllable rate in CDS relative to ADS is also of relevance when comparing temporal statistics.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings concerning rhythmicity are also in line with previous adult studies that have contextualized the temporal regularities of speech within local (utterance level) stress patterns (Arvaniti, 2009;Nolan & Jeon, 2014;Tilsen & Arvaniti, 2013). Indeed, there is recent evidence for local prosodic stress regularities in ADS in different languages (e.g., Inbar et al, 2020;Stehwien & Meyer, 2021). The slower syllable rate in CDS relative to ADS is also of relevance when comparing temporal statistics.…”
Section: Discussionsupporting
confidence: 90%
“…In the same vein, Inbar et al, (2020) found that prosodic units (termed 'intonation units' in their study) produced by adult speakers appear at a roughly constant rate of ~1 Hz. Interestingly, Stehwien and Meyer (2021) analyzed an annotated corpus of radio newscasts in German to show that the prosody of intonational phrases (mapping onto utterances) determined the periodicity of their nested subordinate phrases, suggesting that prosody could have a determining role in shaping the local temporal regularities of adult-directed speech. Overall, the evidence suggests that there is a close overlap between the rhythms of quasi-regular speech units such as stressed syllables and syllables and the timescales at which neurophysiological mechanisms operate to subserve their processing (see Poeppel & Assaneo, 2020 for a comprehensive review on the rhythms of speech production and perception).…”
mentioning
confidence: 99%
“…At the phrase level, phrase rhythm can affect segmentation ( Gee and Grosjean, 1983 ; Martin, 2015 ; Deniz and Fodor, 2019 ; Hilton and Goldwater, 2020 ). There have been various studies aiming to quantify phrase length and rhythmicity ( Clifton et al, 2006 ; Breen, 2018 ; Deniz and Fodor, 2019 ), suggesting that typical intonational phrases are about 1 s in duration ( Auer et al, 1999 ; Inbar et al, 2020 ; Stehwien and Meyer, 2021 ). More specifically, the duration of intonational phrases spans a range between ∼0.5 and 1 s in English (slightly faster in some other languages; Inbar et al, 2020 ; Stehwien and Meyer, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been various studies aiming to quantify phrase length and rhythmicity ( Clifton et al, 2006 ; Breen, 2018 ; Deniz and Fodor, 2019 ), suggesting that typical intonational phrases are about 1 s in duration ( Auer et al, 1999 ; Inbar et al, 2020 ; Stehwien and Meyer, 2021 ). More specifically, the duration of intonational phrases spans a range between ∼0.5 and 1 s in English (slightly faster in some other languages; Inbar et al, 2020 ; Stehwien and Meyer, 2021 ). Prosodic segmentation (here also termed “prosodic chunking”) is based on intonation units that contain specific prosodic cues (such as pauses or pitch contour), which can pace the information flow at the phrasal time scale ( Shattuck-Hufnagel and Turk, 1996 ; Inbar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, low gamma oscillations (⪆30 Hz) have been linked to phonemic processing (Giraud & Poeppel, 2012;Hyafil et al, 2015). More recently, a role of delta oscillations (0.5-2 Hz) in segmenting the input stream at the phrasal time scale has been discussed (Bonhage et al, 2017;Boucher et al, 2019;Ding et al, 2016;Keitel et al, 2018;Meyer et al, 2017;Rimmele et al, 2021;Stehwien & Meyer, 2021).…”
Section: The Role Of Neural Oscillations For the Formation Of Auditory Representationsmentioning
confidence: 99%